Architectural features of transmigration houses in seputhi raman, lampung: a statistical analysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT Descriptive and univariate analyses have demonstrated that the development of houses in transmigration villages depends largely upon the ethnic origin of the householders. Also, the tenacity of the Balinese culture has been shown as having a particular impact on determining the form of houses of Balinese transmigrants. This paper presents the results of multivariate analysis of the architectural features of houses in Seputih Raman transmigration villages in Lampung. The results reveal that while the Javanese, Sundanese, and Banyumese houses are similar in many ways, the features, forms and spatial formations of the Balinese houses are quite distinctive. Further analysis indicates belief as the dominant factor differentiating this group from the others, as reflected in the distinct spatial formation of the Balinese houses.